Ergonomics and safety improvement in a vegetable oil company using REBA and RULA analysis [electronic resource] - Mohd. Nazrin Yasis, 1990-; Masine Md. Tap, supervisor; Fakulti Kejuruteraan Mekanikal (2013)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2013